Analysis of 4H Silicon Carbide Double Implanted MOSFET using Distorted Gaussian Doping Profile in Drift Region for Enhanced Breakdown Voltage and Low Power Dissipation - Jose, Nickson P (My University, 2016)
Silicon Carbide, unlike Silicon, is a Wide Band Gap (WBG) semiconductor that carries with it many properties like high thermal conductivity, high electric field strength and high saturation drift velocity, making it the ideal material for electronic industry. The ability of Silicon Carbide, like Silicon, to easily form high quality native oxide(SiO2), gives it an advantage over other WBG semiconductors like Gallium Nitride and Aluminium Nitride. The research works related to SiC started in late 1980s but received a setback owning to the absence of technology to extract single crystal substrates. However, the above issue and also the lack of reproducible techniques has been taken care of by rapidly maturing extraction technology. The work carried out here on 4H-Silicon Carbide Double Implanted MOSFET(DIMOSFET) is to analyze the performance of the above device related to power dissipation and breakdown voltage for distorted Gaussian doping profile in the drift region. The doping profile which is used here is a more practical profile (that can be obtained by mechanism like Molecular Beam Epitaxy(MBE)). This profile helps to increase the breakdown voltage while at the same time reduces the series parasitic resistance at the lower end of the device thereby lowering the power dissipation, all of which has also been successfully observed in theoretical analysis here.
Master of Technology -VLSI Design
Keywords: Silicon Carbide; Distorted Gaussian Doping Profile; Drift Region; Breakdown Voltage; Double Implanted MOSFET